1975
DOI: 10.1136/hrt.37.5.482
|View full text |Cite
|
Sign up to set email alerts
|

Acute circulatory effects of dopamine in patients with pulmonary hypertension.

Abstract: Twenty-one patients, 11 with normal pulomonary artery pressures and 10 with pulmonary hypertension, had haemodynamic measurements performed before and during dopamine infusion while undergoing cardiac catheterization, in order to evaluate the circulatory effects of dopamine in pulmonary hypertension. In both groups on average, heart rate, pulmonary artery mean pressure, aortic mean pressure, and cardiac index increased significantly, while systemic vascular resistance fell significantly during dopamine admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…This suggests that the dopaminergic receptors stimulated at low doses of DA infusion probably do not induce vasodilation of IPAVA, while the higher concentrations that stimulate ␣-adrenergic receptors could theoretically be preventing IPAVA from fully opening. This seems unlikely, however, because the DA concentration used in the current study has not been shown to cause pulmonary vasoconstriction (20) and is not expected to significantly increase flow or pressure (17), which is supported by our data.…”
Section: Subject Characterization and Lung Functionsupporting
confidence: 79%
See 1 more Smart Citation
“…This suggests that the dopaminergic receptors stimulated at low doses of DA infusion probably do not induce vasodilation of IPAVA, while the higher concentrations that stimulate ␣-adrenergic receptors could theoretically be preventing IPAVA from fully opening. This seems unlikely, however, because the DA concentration used in the current study has not been shown to cause pulmonary vasoconstriction (20) and is not expected to significantly increase flow or pressure (17), which is supported by our data.…”
Section: Subject Characterization and Lung Functionsupporting
confidence: 79%
“…Binding to dopaminergic receptors on renal vascular smooth muscle induces vasodilation (36), as do higher doses of 5 and 10 g•kg Ϫ1 •min Ϫ1 (9). In the pulmonary circulation DA has been shown either to have no effect (20), or to increase (15) or decrease (47) vascular resistance.…”
mentioning
confidence: 99%
“…Milrinone, a selective PDE3 inhibitor, slows intracellular cyclic adenosine monophosphate (cAMP) metabolism, improves inotropy, and facilitates pulmonary vasodilation. It is an attractive agent to use in PH resulting from biventricular failure [ 82 ] and would also be preferable to use in normotensive patients on chronic beta-blocker therapy. Inhaled milrinone has also been investigated for the management of RHF, as it avoids the side effect of systemic hypotension.…”
Section: The Treatment Of Rvfmentioning
confidence: 99%
“…At doses below 16 g kg Ϫ1 min Ϫ1 ), dopamine increases CO without worsening PVR. 37,38 Dobutamine is another inotrope that acts via ␤ 1 receptor stimulation, but may also cause vasodilatation due to ␤ 2 effects. At low doses (5 to 10 g kg Ϫ1 min Ϫ1 ), dobutamine improves PA/RV coupling in animal studies and improves myocardial contractility and PVR in patients with left heart failure.…”
Section: Inotropesmentioning
confidence: 99%